FLUKTUASI GENANGAN AIR LAHAN RAWA LEBAK DAN MANFAATNYA BAGI BIDANG PERTANIAN DI OGAN KOMERING ILIR - Waluyo, Waluyo; Suparwoto, Suparwoto; Sudaryanto, Sudaryanto (Jurnal Hidrosfir Indonesia, 2008)
Research on Lebak (fresh water) convered 100 hectars that has been conducted at Tanjung Alai, Ogan Komering Ilir district South Sumatera. This research consist of land characteristics, type and properties of Lebak, particularly zonification of Lebak type, length and hight of flooding which determined Lebak zone, fluctuation of flooding, crop scheduling of rice and soybean. Main problem of Lebak were hight flooding in the wet season and drought in the dry season on the long flooding condition it do not able to be planted cash crops. Result showed that research site can be divided into 3 type of Lebak; first, shallow Lebak has average hight flooding –97 cmto 55 cm, length flooding period 5 months and time schedule of planting since January up to May and June until Oktober; second, medium Lebak has average hight flooding – 50 cm to 100 cm, 9 months flooding period, and time schedule of planting since February up to June and Juli until November; third, deep Lebak has average hight flooding –32 cm up to 140 cm, 10 months flooding period and time schedule of planting since Januari up to June and Juli until November.